2015
DOI: 10.1039/c4nr06186a
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamonds from coal under ambient conditions

Abstract: Coal is the most abundant energy resource, but it is only useful for producing energy via combustion due to its structural characteristics. However, coal is also inexpensive and is the most plentiful and readily available carbon source material for the production of nanodiamonds compared with the most widely used solid carbon source, high-purity graphite, and the high-purity hydrocarbon gas precursor, methane. Here, we report a simple and green top-down strategy for synthesizing nanodiamonds with a cubic phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 52 publications
6
49
0
Order By: Relevance
“…It turned out that the peaks were located at 558.1 and 563.3 nm in the emission spectrum ( Fig. 6C ), corresponding to the C 2 swan band for Δ v = −1 ( 28 ) arising from transitions between the electronic states d 3 Π g and a 3 Π u ( 29 ) and providing straightforward evidence for the formation of C 2 molecules in our case. In addition, we collected the spectra of the other kinds of solvent that were similar to alcohol, including methanol, acetone, n -propanol, and isopropanol ( Fig.…”
Section: Discussionmentioning
confidence: 55%
“…It turned out that the peaks were located at 558.1 and 563.3 nm in the emission spectrum ( Fig. 6C ), corresponding to the C 2 swan band for Δ v = −1 ( 28 ) arising from transitions between the electronic states d 3 Π g and a 3 Π u ( 29 ) and providing straightforward evidence for the formation of C 2 molecules in our case. In addition, we collected the spectra of the other kinds of solvent that were similar to alcohol, including methanol, acetone, n -propanol, and isopropanol ( Fig.…”
Section: Discussionmentioning
confidence: 55%
“…[ 16,17 ] X-ray diffraction (XRD) patterns of the as-prepared NDs and graphite precursor are presented in Figure 1 a, and indicate the phase transformation of graphite (PDF#26-1079) to diamond (PDF#43-1104). [ 16,17 ] X-ray diffraction (XRD) patterns of the as-prepared NDs and graphite precursor are presented in Figure 1 a, and indicate the phase transformation of graphite (PDF#26-1079) to diamond (PDF#43-1104).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[ 2 ] Moreover, the narrow direct band gap of Cu 2 O of 1.9-2.4 eV confers it with excellent light-harvesting ability. [ 16,17 ] The abundant surface functional groups and small fraction of sp 2 -hybridized C vests the prepared ND with a broad absorption spectrum and up-and down-conversion PL, resulting in good utilization of solar energy even in the near-infrared (NIR) region. In this contribution, we report that ND-embedded Cu 2 O nanocrystals (NDs-Cu 2 O) exhibit high photocatalytic HER performance and photostability.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been reported on the synthesis of carbon-based dots from coal and humic substances which are rich in nanocarbon domain. These carbon-based materials are composed of organic compounds which are formed during the coalification or humification process 3 5 . Coal is being considered as an abundantly available precursor for the synthesis of nanotubes, nanoballs, carbon nanodots, onion-like fullerene and graphene quantum dots (GQDs).…”
Section: Introductionmentioning
confidence: 99%
“…Review of the literature reveals that the GQDs and carbon dots synthesized from lignite form a stable suspension with high colloidal stability 7 . Majority of the studies report the utilization of only the supernatant part of the sample and the residue part is discarded 3 , 4 , 9 . Whether these residuals can be converted to carbon dots with unique properties is worth investigating owing to the impact on the cost of production.…”
Section: Introductionmentioning
confidence: 99%